Motives for Sports Participation Among Sport Science and Recreation Malay Student-Athletes, University Technology Mara (UITM), Shah Alam - Parnabas, Vincent (2002)
There is a need to conduct a research on sport participation with those who had already taken part in sports, especially on Malay student-athletes because motives may not only be the reason why people start taking part in sports, but also often they are the reason why people continue to participate in sports. Furthermore, by understanding the motives of student-athletes to participate in sports, an effort can be made, in structuring the sports environment so that needs of the Malay student-athletes can be met. The study was concerned with sport participation motives among Malay student-athletes of Sport Science and Recreation Faculty at University Technology MARA (UiTM). The purpose of this study was to identify the main motives for sport participation. The study also determined the differences in motive by gender (male and female), courses (Diploma and Degree) and level of representation in sports (school, university, district, state and country). The research employed quantitative research methodology based on responses from questionnaire. Purpose of Sport Questionnaire designed by Duda (1989) was employed as instrument. The sample consisted of 300 Malay student-athletes, who had participated in sport either at school, university, district, state or country level. A five-point rating Likert-type scale was used. The statistical package SPSS was used for data analysis. Percentages, means and standard deviations were computed for the criteria indicators. Independent t -tests and ANOYA were computed to determine significance between means of the groups, and were used to test for significant.